2012
DOI: 10.1016/j.puhe.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Is there a robust relationship between neighbourhood food environment and childhood obesity in the USA?

Abstract: SUMMARY Objectives To examine the robustness of the relationship between neighbourhood food environment and youth body mass index (BMI) percentile using alternative measures of food environment and model specifications. Study design Observational study using individual-level longitudinal survey data of children in fifth and eighth grades merged with food outlet data based on student residential census tracts. Methods The relationship between food environment and BMI was examined with two individual outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 30 publications
3
83
1
Order By: Relevance
“…In 2011, Leung et al 114 suggested that residents with more produce vendors or farmers markets nearby had a lower risk of being overweight/ obese. On the other hand, Shier et al 115 found no consistent evidence to support the idea that more grocery stores lowered youth BMI or that greater exposure to fast-food restaurants, convenience stores, and small food stores increased BMI.…”
Section: Built Environmentmentioning
confidence: 97%
“…In 2011, Leung et al 114 suggested that residents with more produce vendors or farmers markets nearby had a lower risk of being overweight/ obese. On the other hand, Shier et al 115 found no consistent evidence to support the idea that more grocery stores lowered youth BMI or that greater exposure to fast-food restaurants, convenience stores, and small food stores increased BMI.…”
Section: Built Environmentmentioning
confidence: 97%
“…The presence of a supermarket in the neighborhood is controversial: on the one hand, there is a great variety of fresh and healthy foods at competitive prices 38 ; on the other hand, there is also a great variety of cheap unhealthy foods, such as soda, sweets, snacks, and frozen dinners 39 . Moreover, advertising encourages people to buy products that are not on promotion, increasing their food expenditures 31 .…”
Section: Discussionmentioning
confidence: 99%
“…(30,31) . Future research could help answer this question by considering together areas in which people work as well as where they live, which we did not do in the present study.…”
Section: Discussionmentioning
confidence: 99%